2020
DOI: 10.1101/2020.06.10.20127175
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Excess deaths in people with cardiovascular diseases during the COVID-19 pandemic

Abstract: Background: Cardiovascular diseases(CVD) increase mortality risk from coronavirus infection(COVID-19), but there are concerns that the pandemic has affected supply and demand of acute cardiovascular care. We estimated excess mortality in specific CVDs, both direct, through infection, and indirect, through changes in healthcare. Methods: We used population-based electronic health records from 3,862,012 individuals in England to estimate pre- and post-COVID-19 mortality risk(direct effect) for people with incid… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 21 publications
(35 reference statements)
0
18
0
1
Order By: Relevance
“…29 Where reported, recovery of activity has generally been slow; for example, in hospitals in China, CVD activity remained below pre-COVID-19 levels for 2–3 months, even after easing lockdown. 10 To our knowledge, the present report is the first UK study to have recorded overall and cardiovascular hospital activity over a long enough period since lockdown to show the beginning of recovery in some measures and is the only study we are aware of to provide analyses of these via an online tool designed to include data from additional hospitals and regular updates over the months ahead.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…29 Where reported, recovery of activity has generally been slow; for example, in hospitals in China, CVD activity remained below pre-COVID-19 levels for 2–3 months, even after easing lockdown. 10 To our knowledge, the present report is the first UK study to have recorded overall and cardiovascular hospital activity over a long enough period since lockdown to show the beginning of recovery in some measures and is the only study we are aware of to provide analyses of these via an online tool designed to include data from additional hospitals and regular updates over the months ahead.…”
Section: Discussionmentioning
confidence: 94%
“… 8 9 In the UK, studies have reported reductions in activity across CVDs. 10 11 Moreover, official national statistics show an excess of non-COVID-19 and CVD deaths, 12 13 as well as a reduction in emergency department (ED) attendances for cardiac presentations. 14…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, we only have access to empirical cancer service change data from eight hospitals in the UK. While the data may be a representative sample of the UK population, and patterns of decline in service change is corroborated in another study, 42 more widespread access to other trusts may be beneficial to ascertain national and regional effects.…”
Section: Strengths Of This Studymentioning
confidence: 85%
“… 4 Moreover, as countries plan strategies to exit or scale down lockdown, policies to tackle COVID-19 may have unintended consequences on health care and outcomes for non-COVID-19 diseases, which we reported for cancer and cardiovascular diseases (CVDs). 5 , 6 …”
Section: Introductionmentioning
confidence: 99%